Proficiency-Based Instruction in Reading: A Teacher Education Module. Sample Materials Chinese (Mandarin), English as a Second Language (Beginning and Advanced), French, German, Japanese, Russian, Spanish, and Thai - Phillips, June K.; Indiana Univ. of Pennsylvania, Indiana ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Sample materials demonstrating the use of a five-step procedure for teaching reading in another language, are provided as part of an inservice program for teachers. The manual includes passages, class activities, and instructional suggestions for each step of the learning process in these languages: Mandarin Chinese (intermediate), English as a second language (beginning and advanced levels), French (secondary level), German, Japanese (elementary/intermediate), Russian, Spanish (intermediate), and Thai (intermediate). The five steps in the instructional plan include: prereading or preparation, skimming and/or scanning, intensive reading/decoding, comprehension check/evaluation, and transferable or integrating skills. (MSE)
Sponsoring Agency: Office of International Education (ED), Washington, DC.
Contract Number: G008402271.
ERIC Note: For related documents, see FL 015 423-424.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Advanced Courses; Classroom Techniques; Competency Based Education; English (Second Language); French; German; Inservice Teacher Education; Instructional Materials; Introductory Courses; Japanese; Mandarin Chinese; Reading Instruction; Reading Strategies; Russian; Second Language Instruction; Spanish; Teacher Workshops; Teaching Guides; Thai; Guides, Classroom -- Teacher